Electricity: Domestic Consumption Versus Export - Pradhan, Gyanendra Lal (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Due to its unique geography, Nepal is gifted with very high hydropower potential, far greater than generally accepted figure of 83,000 MW and 43000 MW of theoretical and techno-financial viability. Our neighbors India, Pakistan and Bangladesh are suffering from huge power shortages. There is no point in debating whether Nepal’s hydropower should be for domestic consumption or for export because the potential of generating hydropower in Nepal is far greater than its domestic consumption, even in 2050. Due to the lack of appropriate policies, however, Nepal suffers from long hours of load shedding. The government policy to subsidize petroleum products was a big mistake for, like Bhutan, electricity should have been the cheapest source of energy. Politicians are focusing mostly in export oriented projects; whereas, higher importance should have been given to projects for domestic consumption. We should aim at producing twice the needed internal demand. Nepal is poised to reap huge benefits from hydropower. Key words: Hydropower; domestic consumption; load shedding; export; Nepal doi: 10.3126/hn.v3i0.1913 Hydro Nepal Journal of Water, Energy and Environment Issue No. 3, July 2008. Page: 16-18